KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DAN PANJANG TUNGKAI TERHADAP KEMAMPUAN GRAB START ATLET PERKUMPULAN RENANG TIRTA KALUANG PADANG - AJI PUTRA; Anton Komaini (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2019)
The research problem was the low Grab Start ability in Swimming Pool Athletes Tirta Kaluang Padang. This research is a correlational study which aims to determine how much the contribution between the explosive power of leg muscles and leg length to Grab Start Ability In Swimming Pool Athletes Tirta Kaluang Padang Association. This research is included in the type of correlational research. The population in this study were Swiming Pool Athletes Tirta Kaluang Athletes Association totaling 25 people. Sampling in this study was carried out by purposive sampling technique. So, the sample in this study was 12 people. Data is collected using measurements on all three variables. The variable grab start ability is measured by the grab start ability test, the variable explosive power of leg muscle is measured by a standing broad jump test and the variable leg length is measured by the Leg Length Test. Data were analyzed using product moment. The results of the data analysis were obtained: (1) From the results of the Explosion Power of leg muscle has a significant contribution to the grab start ability athletes at the Swiming Pool Athletes Tirta Kaluang Athletes Association, marked by From the results obtained, the leg length has a significant contribution to the grab start athletes at the Swiming Pool Athletes Tirta Kaluang Athletes Association, marked by the results obtained by tcount = 3.19> t table = 1,833 and contribute as much as 50%. (3) There is a significant contribution together between Leg Muscle Explosion Power and Leg Length to the Capability of Tirta Kaluang Pool Athletes' grab start ability, marked by the results obtained by Fcount = 10.19> Ftable = 4.26 and make a contribution as hard as 69%.